Ação revocatória falimentar - Fazolo, Gisele (2009)
The Bankruptancy Revocatory Action inserts itself in the context of the bankruptancy process and it depends on the decretory bankruptcy judicial decision to have pertinence, for that, the present study begins with bankruptancy law notion and, soon afterwards, applicable principles to the bankruptancy process. The Action, object of this study, is to turn ineffective acts in relation to the bankrupted object and it possesses two possible modalities: Revocatory Action for Inefficacy of the Act and Revocatory Action for Repeal of Acts, foreseen in the articles 129 and 130 of the Law 11.101/2005, respectively. Besides the common dispositions to the two modalities of actions, the differences among them are approached, and, finally, it is made a comparison between the Bankruptancy Repeal Action and the Civil Revocatory Action (Pauliana Action), as well as the possibility or non of changeble and cumulativity among the Bankruptancy Revocatory Action and the Civil Revocatory Action in the Bankruptcy Court.